Rekonstruksi Penalaran Hukum Islam dari Fiqih Klasik ke Konteks Digital: Pendekatan Mazhab Komparatif Sebagai Basis Moderasi Keagamaan - Faizin, Slamet Imam; Luthfiana, Aas; Pramono, Dwi; Aziza, Fitrotul; Siyono, Siyono (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The development of digital technology has changed the landscape of religious knowledge production and authority, including in the field of Islamic law. This transformation has opened up broad access to fiqh discourse, but at the same time has given rise to serious challenges in the form of fragmentation of scientific authority, simplification of legal reasoning, and the strengthening of polarization and exclusive religious attitudes. This article aims to reconstruct Islamic legal reasoning from the classical fiqh framework to the digital context by placing the comparative madhhab approach as the epistemological basis for strengthening religious moderation. The main issue of this research focuses on how the methodology of cross-madhhab ijtihad can be systematically adapted to respond to the dynamics of digital diversity without eliminating the scientific and ethical legitimacy of Islamic law. This research uses a qualitative method based on literature study with a normative, comparative, and conceptual hermeneutic approach. Data were obtained from the uṣūl al-fiqh and classical fiqh books of the four Sunni madhhabs, contemporary academic literature, and religious moderation policy documents. The results of this study indicate that the comparative approach is capable of reconstructing Islamic legal reasoning in the digital context through the strengthening of epistemological pluralism, the integration of adaptive istinbāṭ methodologies to the digital social context, and the revitalization of scientific authority based on methodological transparency. The novelty of this research lies in the formulation of a framework for digital Islamic legal reasoning that makes fiqh muqāran an operational and contextual instrument of religious moderation. This research has implications for strengthening Islamic legal literacy, developing adaptive religious education, and forming an inclusive, critical, and balanced digital religious ecosystem.